The Oxford Encyclopedia of American Cultural & Intellectual History. - Odom, Brian (Booklist, 2013)
The article reviews the book "The Oxford Encyclopedia of American Cultural and Intellectual History" edited by Joan Shelley Rubin and Scott E. Casper.